Shortcut to chemically accurate quantum computing via density-based basis-set correction - Diata Traore; Olivier Adjoua; César Feniou; Ioanna-Maria Lygatsika; Yvon Maday; Evgeny Posenitskiy; Kerstin Hammernik; Alberto Peruzzo; Julien Toulouse; Emmanuel Giner; Jean-Philip Piquemal (Communications Chemistry)
Abstract Using GPU-accelerated state-vector emulation, we propose to embed a quantum computing ansatz into density-functional theory via density-based basis-set corrections to obtain quantitative quantum-chemistry results on molecules that would otherwise require brute-force quantum calculations using hundreds of logical qubits. Indeed, accessing a quantitative description of chemical systems while minimizing quantum resources is an essential challenge given the limited qubit capabilities of current quantum processors. We provide a shortcut towards chemically accurate quantum computations by approaching the complete-basis-set limit through coupling the density-based basis-set corrections approach, applied to any given variational ansatz, to an on-the-fly crafting of basis sets specifically adapted to a given system and user-defined qubit budget. The resulting approach self-consistently accelerates the basis-set convergence, improving electronic densities, ground-state energies, and first-order properties (e.g. dipole moments), but can also serve as a classical, a posteriori, energy correction to quantum hardware calculations with expected applications in drug design and materials science.